Pengembangan Media Board Game Berbasis Gamified Learning Pada Materi Membandingkan dan Mengurutkan Bilangan Siswa Kelas III B SD Negeri Ngaliyan 03 Kota Semarang - Prismarini, Fernandia; Witanto, Yuli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics instruction on comparing and ordering whole numbers up to 1,000 in elementary school still faces various challenges. Observations indicate that instruction is still dominated by lecture-based methods and written exercises. This makes it difficult for students to understand the concept of numerical value and to correctly determine the order and comparison of numbers. These conditions result in low student engagement and motivation. This study aims to develop a board game-based learning medium using gamified learning, assess the medium’s feasibility, and test its effectiveness in teaching the topic of comparing and ordering whole numbers up to 1,000 for third-grade elementary school students. This study employs the Research and Development (R&D) method, using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were third-grade students in Class 3B at Ngaliyan 03 Public Elementary School in Semarang City. Data collection techniques included observation, interviews, questionnaires, expert validation, and learning outcome tests. The results showed that the gamified learning-based board game educational medium was rated as highly feasible based on a 92.5% rating from the media expert, a 92.5% rating from the content expert, and a “very good” user response category. The results of the effectiveness test showed an improvement in student learning outcomes after using the media, as indicated by the difference in pretest and posttest scores and an increase in the N-Gain score of 78.19%, categorized as effective. Thus, the gamified learning-based board game media is deemed highly suitable and effective for use in mathematics instruction on the topic of comparing and ordering whole numbers up to 1,000. Keywords: Natural Numbers, Board Game, Gamified Learning, Comparing Numbers, Ordering Numbers